2012 IEEE Seventh International Conference on Global Software Engineering 2012
DOI: 10.1109/icgse.2012.29
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Reviews in Distributed Software Development: A Tertiary Study

Abstract: Distributed Software Development (DSD) emerged from the need to achieve geographically distant customers and currently, allows organizations have global customers and other benefits. This scenario has given rise to new Software Engineering challenges resulting from DSD particularities. Several Systematic Reviews were conducted to address these new challenges. The objective of this paper is to categorize systematic reviews conducted in DSD context. We used the systematic review method to identify SLRs (Systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…As future work, they intended to propose a combinatorial optimization-based model involving classical task scheduling problems. Marques et al [18] also performed a tertiary review applying the systematic review method on systematic reviews that address the DSD issues. The study revealed that most of the work focuses on summarizing the current knowledge about a particular research question, and the amount of empirical studies is relatively small.…”
Section: Task Allocation In Distributed Software Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As future work, they intended to propose a combinatorial optimization-based model involving classical task scheduling problems. Marques et al [18] also performed a tertiary review applying the systematic review method on systematic reviews that address the DSD issues. The study revealed that most of the work focuses on summarizing the current knowledge about a particular research question, and the amount of empirical studies is relatively small.…”
Section: Task Allocation In Distributed Software Developmentmentioning
confidence: 99%
“…Its complexity increases in distributed development software environment, where we must consider additional factors inherent to distribution [18]. The assignment of tasks can be seen as a critical activity for success in project management of distributed development.…”
Section: Introductionmentioning
confidence: 99%
“…The allocation of tasks is a critical activity for project planning. This allocation becomes even more complex in a distributed context where we must consider factors inherent to distribution [14]. The allocation of tasks to remote teams can be seen as a fundamental activity for the success of a distributed project.…”
Section: Introductionmentioning
confidence: 99%
“…They intended to propose a combinatorial optimization-based model involving classical task scheduling problems. Marques et al [24] also performed a tertiary review applying the systematic review method on systematic reviews that address the DDS issues.…”
Section: Task Allocation In Ddsmentioning
confidence: 99%
“…On the other hand, the distribution brings many challenges, such as language and time zone differences and increased complexity of coordinating and controlling the project [25]. In this context, the allocation of tasks is an even more critical activity for project planning because of the distribution [24]. The distribution of tasks to remote teams can be seen as a fundamental activity for the success of a distributed project.…”
Section: Introductionmentioning
confidence: 99%